2022
DOI: 10.7759/cureus.28015
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Gingival Pigmentation Patterns and Skin Color and Its Co-relation With Serum Ferritin Levels in Thalassemic Patients

Abstract: Background: Patients with β-thalassemia major (β-TM), a genetic issue due to hemoglobin (Hb) synthesis disorder, require life-long erythrocyte transfusion. The purpose of this study is to evaluate and compare gingival pigmentation and skin color with serum ferritin levels of patients with β-TM, using the Dummett's oral pigmentation index (DOPI) and Fitzpatrick skin scale, respectively. Methods: A total of 100 patients were monitored at a thalassemia care center. Each patient's gingival pigmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Gajjar and his colleagues studied the association of ferritin levels and gingival and skin pigmentation degree in beta thalassemia patients. They had concluded that gingival hyperpigmentation and skin color changes had been seen among older multi‐transfused patients, also had noticed a significant relation between ferritin levels and gingival pigmentations and skin color changes 10 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gajjar and his colleagues studied the association of ferritin levels and gingival and skin pigmentation degree in beta thalassemia patients. They had concluded that gingival hyperpigmentation and skin color changes had been seen among older multi‐transfused patients, also had noticed a significant relation between ferritin levels and gingival pigmentations and skin color changes 10 …”
Section: Discussionmentioning
confidence: 99%
“…They had concluded that gingival hyperpigmentation and skin color changes had been seen among older multi-transfused patients, also had noticed a significant relation between ferritin levels and gingival pigmentations and skin color changes. 10 Although good amounts of data are available regarding the diagnosis and management of sickle cell disease, however, there is a lack in the literature concerning management of this rare phenotype. Antibiotic prophylaxis was recommended for this patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations